Morphology and size of soot from gas flares as a function of fuel and water addition. (1st November 2020) - Trivanovic, Una; Sipkens, Timothy A.; Kazemimanesh, Mohsen; Baldelli, Alberto; Jefferson, A. Melina; Conrad, Bradley M.; Johnson, Matthew R.; Corbin, Joel C.; Olfert, Jason S.; Rogak, Steven N.
Graphical abstract: Highlights: Correlation between fuel higher heating value and degree of soot graphitization. Novel approach to two-dimensional mass-mobility and effective density distributions. No change in soot primary particle size to aggregate size relationship due to fuel. Abstract: A large-scale, laboratory turbulent diffusion flame was used to study the effects of fuel composition on soot size and morphology. The burner and fuels are typical of those used in the upstream oil and gas industry for gas flaring, a practice commonly used to dispose of excess gaseous hydrocarbons. Fuels were characterized by their carbon-to-hydrogen ratio (from 0.264 to 0.369) and their volumetric higher heating value (HHVv) (from 35.8 to 75.2 MJ/m 3 ). Transmission electron microscopy (TEM) was used to assess primary particle and aggregate size, showing that the scaling of primary particle size to aggregate size was roughly the same for all of the considered fuels ( d p  = 16.3( d a, 100 [nm]/100) 0.35 ). However, fuels with higher HHVv produced substantially larger soot aggregates. A scanning mobility particle sizer (SMPS) was also used (i) to measure mobility diameter distributions and (ii) in tandem with a centrifugal particle mass analyzer (CPMA) to determine the two-dimensional mass-mobility and effective density-mobility distributions using a new inversion approach. The new approach was shown to improve internal consistency of inferred morphological parameters, though with a shift relative to median-based analysis of the tandem data. Raman spectroscopy was used to quantify the degree of graphitization in the soot nanostructure. The addition of water to the fuel consistently reduced the soot yields but did not affect other morphological parameters. Larger aggregates also tended to have larger primary particles and higher Raman D/G ratios suggesting larger graphitic domains.